HUBUNGAN KOMPOSISI SARAPAN DENGAN KADAR GULA DARAH DAN FUNGSI KOGNITIF PADA MAHASISWA KEDOKTERAN (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2018)
Background: Breakfast is the first meal in the early days and is mentioned as the most important food in a day. Breakfast aims to meet nutritional needs in the morning, as part of a balanced and beneficial nutritional fulfillment in helping prevent hypoglycemia, stabilizing blood glucose levels, and preventing dehydration after fasting throughout the night. Some studies suggest that breakfast habits can affect cognitive function, including concentration, learning performance, and memory. Method: The research method is cross sectional analytic with sampling is done by consecutive sampling method, each subject that meets the research criteria is included as research subject until the required amount is met. Interviews, anthropometric examination, blood glucose examination and cognitive function assessment were performed on the respondents. Result: Nutritional status based on body mass index (BMI) of study subjects was 22.07 ± 4.11, 60% of subjects included in normal nutritional status category. While the breakfast energy intake in this study obtained 361.57 ± 10.8 kcal which sufficient 15-20% of total calorie intake. In this study there was no relationship between breakfast composition with blood glucose level (p> 0,05) and cognitive function (p> 0,05) Conclusion: In this study there was no significant relationship between breakfast composition with glucose level and cognitive function in medical students.